2015
DOI: 10.1111/head.12493
|View full text |Cite
|
Sign up to set email alerts
|

Diamine Oxidasers10156191 and rs2052129 Variants Are Associated With the Risk for Migraine

Abstract: Our findings, which should be framed as hypothesis generating, suggest that DAO genotypes and allelic variants are associated with the risk for migraine in Caucasian Spanish people, especially in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 45 publications
(92 reference statements)
4
47
1
Order By: Relevance
“…Previous works suggest that imbalances in histamine degradation capacity may associate with the development of migraine and atopic dermatitis [3, 4], but little is known on the role of DAO in CSU. Taken together, our data suggest that DAO activity could be a cofactor in the development of CSU clinical manifestations and that DAO supplementation could contribute to a better disease control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works suggest that imbalances in histamine degradation capacity may associate with the development of migraine and atopic dermatitis [3, 4], but little is known on the role of DAO in CSU. Taken together, our data suggest that DAO activity could be a cofactor in the development of CSU clinical manifestations and that DAO supplementation could contribute to a better disease control.…”
Section: Discussionmentioning
confidence: 99%
“…Histamine lies downstream the pathogenic cascade that leads to the development of itch and wheals in CSU as well as in most immediate-type hypersensitivity reactions, since it prompts vasodilation and increased vascular permeability [2]. Furthermore, histamine-related events have been implicated in the pathogenesis of other diseases such as atopic dermatitis and migraine [3]. Systemic and local levels of histamine are influenced by mast cell release, gastrointestinal absorption and catabolic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Recruitment of patients was done in the general neurological clinics of 3 University Hospitals during the period between September 2006 and August 2007 (the onset of migraine attacks was under age 15 years in 113 patients, positive family history for migraine was reported by 147 patients, and 98 of them had MWA). Most of these patients have participated previously in other genetic association studies reported by our group …”
Section: Methodsmentioning
confidence: 99%
“…Most of these patients have participated previously in other genetic association studies reported by our group. 3,[53][54][55][56][57][58] Control individuals were healthy Caucasian Spanish subjects recruited from professors or students from the University of Extremadura, who did not suffer from migraine or other headache types, and have not familial history of migraine. They were interviewed by three physicians (Drs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation